Reading early modern women's writing - Salzman, Paul (Oxford University Press, 2006)
Most people, even within the area of English literature, are unaware of how much writing women produced in the 16th and 17th centuries. This book offers an outline of that writing, and also looks at how it was read and reproduced through succeeding centuries.